Immunological and pathobiological characteristics of a novel live Salmonella Typhimurium-vectored Campylobacter vaccine candidate for layer chickens - Mcdonald, Jamieson B.; Gan, Emily; Cain, Joel; Thoduka, Sapna G.; Lee, Joseph; Wade, Ben; Mauri, Marta; Cuccui, Jon; Wren, Brendan W.; Packer, Nicolle H.; Londrigan, Sarah L.; Fritzlar, Svenja; et al. (Frontiers in Veterinary Science, 2025)
IntroductionSpotty liver disease (SLD) poses a significant economic and animal welfare threat to the global cage-free egg industry, primarily due to infection by the emerging pathogen Campylobacter hepaticus. SLD can lead to a significant decline in egg production and increased mortality rates. Antibiotics remain the most effective measure for controlling the disease. However, the rise of antibiotic resistance is a growing global concern for public health, promoting efforts to reduce antibiotic usage in animal production. Poultry vaccination offers an alternative approach to decreasing C. hepaticus levels. Although autogenous vaccines are in use in some countries with limited efficacy, no vaccine is currently licensed for widespread use.MethodsThis study developed and characterized a live Salmonella Typhimurium vector strain designed to deliver the conserved Campylobacter N-glycan heptasaccharide as a target antigen against C. hepaticus.ResultsThe replacement of the S. Typhimurium aroA gene with the Campylobacter pgl locus attenuated the vaccine strain, allowing the conjugation of the heptasaccharide to S. Typhimurium endogenous lipopolysaccharide (LPS). Commercial layer hens vaccinated with the S. Typhimurium strain producing the Campylobacter heptasaccharide induced significantly higher IgY antibody titres specific to the Campylobacter heptasaccharide compared to the birds vaccinated with the vector strain not expressing the heptasaccharide. Modification of the S. Typhimurium endogenous LPS with the heptasaccharide had no significant impact on IgY antibody responses against S. Typhimurium.DiscussionThis study provides evidence that using S. Typhimurium to deliver Campylobacter heptasaccharide is a feasible approach to providing bi-valent immunogenicity against both S. Typhimurium and C. hepaticus.